Music Arts Teachers' Strategies in Developing Students' Creativity: A Descriptive Study at the UPT of SMP Negeri 3 Lintau Buo Utara - Amalyah, Nesya; Astuti, Fuji; Ardipal, Ardipal (Journal of English Language and Education, 2026)
Music arts education plays a strategic role in developing the creativity of junior high school students, but is often hampered by monotonous approaches and limited facilities. This study aims to describe the strategies of music arts teachers in developing student creativity at the UPT SMP Negeri 3 Lintau Buo Utara. Using a descriptive qualitative approach, the study population consisted of music arts teachers and students in grades VII-VIII, with a purposive sample of one teacher and 6-8 students. Instruments included observation, semi-structured interviews, and documentation, analyzed through data reduction, narrative presentation, and triangulation. The results show that teachers implemented direct practice strategies (learning by doing), creative exploration, group work, and simple media such as recorders and pianicas, increasing active involvement and student confidence. It was concluded that these strategies were effective in creating conducive learning, although limited to generalizations in the local context.